Computer-assisted correction of incongruent distal radioulnar joints in patients with symptomatic ulnar-minus variance. (September 2022) - Estermann, Lea; Urbanschitz, Lukas; Reissner, Lisa; Schweizer, Andreas
Our study described a computer-assisted, three-dimensional (3-D), planned surgical technique of a radial shortening osteotomy. The osteotomy of the distal radius was planned with computer assistance on 3-D bone models based on computed tomography data. The objective was to maximize the contact zone of the sigmoid notch with the ulnar head. Between 2012 and 2020 we treated 14 wrists in 11 patients with symptomatic ulnar-minus variance with a mean follow-up of 44 months (range 8 to 98) and a mean age of 28 years (range 19 to 38). Postoperatively, patients showed a decrease in pain at rest and during effort (numeric rating scale from 4.4 to 0 and 7.5 to 4.5, respectively). The range of motion postoperatively was similar to the contralateral side. Grip strength increased from 24 kg to 30 kg. The Disability of the Arm, Shoulder, and Hand and the Patient-Rated Wrist Evaluation scores were 28 and 35 postoperatively, respectively. Our technique of 3-D computer-assisted distal radioulnar joint reconstruction led to a pain reduction and improvement of the hand function in patients with symptomatic ulnar-minus variance. Level of evidence: IV